FILSAFAT KETUHANAN: LOGIKA KETUHANAN ALLAH - Arif Aulia Rizki; Nunu Burhanuddin (CV. Adiba Aisha Amira, 2023)
God himself is an omnipotent being and the principle of belief and confidence. Many experts have expressed the meaning of God, but the problem is that there is no agreement regarding the meaning of God itself, even among philosophers. Discussing God is a very basic problem in the study of philosophy, especially in the philosophy of religion. The study of God itself is a study that will never be finished until the end of the day. But the problem is, in the study of philosophy itself, God is a big question mark, namely does God exist? and how does God exist? These two questions have always been big question marks in the study of philosophy and have made people and philosophers think about them. The problem is even worse, since ancient times many have even claimed that they are gods. If we are good Muslims, we should not question such things or even claim to be God. The duty of a Muslim is only to believe in Allah, feel his power and only worship Him. So with questions like that, there are many ideas about God and it becomes an opening for other people to come in and claim to be God. For this reason, this research aims to answer similar questions using logic so that all humans believe that there is only one God, namely Allah SWT